CHARACTERISTICS OF HERBIVORY/WOUND-ELICITED ELECTRICAL SIGNAL TRANSDUCTION IN TOMATO - Chaoyi HU, Siqi DUAN, Jie ZHOU, Jingquan YU (Frontiers of Agricultural Science and Engineering, 2021)
<ListItem><ItemContent> • Herbivory and mechanical wounding elicited electrical signals. </ItemContent></ListItem><ListItem><ItemContent> • Petiole wounding elicited stronger electrical signals than did leaflet wounding. </ItemContent></ListItem><ListItem><ItemContent> • Leaflet wounding elicited electrical signals and JA signaling within a compound leaf. </ItemContent></ListItem><ListItem><ItemContent> • GLR3.3 and GLR3.5 mediated leaflet-to-leaflet electrical signal transduction. </ItemContent></ListItem><ListItem><ItemContent> • JA synthesis and Helicoverpa armigera resistance were reduced in glr3.3/3.5 plants. </ItemContent></ListItem> Electrical signals commonly occur in plants in response to various environmental changes and have a dominant function in plant acclimation. The transduction of wound-elicited electrical signals in the model plant species Arabidopsis has been characterized but the characteristics of electrical signal transduction in response to herbivory or wounding in crop species remain unknown. Here, the features of electrical signals elicited by insect herbivory and wounding in tomato were investigated. Unlike those in Arabidopsis, wounding tomato leaves did not cause leaf-to-leaf electrical signal transduction. In contrast, electrical signals elicited in response to petiole wounding were stronger and more strongly transduced. Leaflet wounding also activated electrical signal transduction and jasmonic acid (JA) signaling within the whole compound leaf. It was also demonstrated that tomato glutamate receptor-like 3.3 (GLR3.3) and GLR3.5 mediated leaflet-to-leaflet electrical signal transduction. Herbivory-induced JA accumulation and Helicoverpa armigera resistance were reduced in glr3.3/3.5 plants. This work reveals the nature of electrical signal transduction in tomato and emphasizes the key roles of GLR3.3 and GLR3.5 in electrical signal transduction and JA signaling activation.